Determinants of Government Procurement Fraud Prevention with Organizational Commitment and Ethical Culture as Moderating Variables - Sitti Mukhtia Ulfah; Mohamad Khoiru Rusydi; Yeney Widya Prihatiningtias (AIBPM Publisher, 2024)
This study aims to analyze the various factors that influence the prevention of procurement fraud, including the implementation of the Anti-Bribery Management System (ABMS), Government Internal Control System (SPIP), and the role of the Internal Compliance Unit (UKI), with organizational commitment and ethical culture as moderators. It employs a quantitative causal approach, with data collected through surveys and analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results demonstrate that the implementation of ABMS, SPIP, and UKI positively impacts the prevention of procurement fraud. Organizational commitment and ethical culture strengthen the influence of SPIP implementation, while ethical culture weakens the role of UKI in preventing fraud. ABMS, SPIP, and UKI are crucial in fraud prevention, but their effectiveness is enhanced by a strong commitment to ethics. While organizational commitment strengthens SPIP's preventive effects, a strong ethical culture may reduce the reliance on UKI in fraud prevention. These findings underscore the importance of comprehensive anti-fraud measures such as the implementation of ABMS, SPIP, and the establishment of UKI in preventing procurement fraud.